2018
DOI: 10.1097/md.0000000000009763
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of blood glucose distribution characteristics in a health examination population in Chengdu from 2010 to 2016

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Our predictive models are in good agreement with the latter and are more plausible in terms of sustaining the NP cell population which has been shown to experience significant cell death when glucose drops below 0.5 mM for more than 3 days 38,39,109 . Even with an array of predicted and measured glucose concentrations (0.25‐3.5 mM) it is a relatively narrow range confined by the upper supply limit of blood glucose levels (2.6‐6.1 mM) 32 . Despite this more than 50% of publications utilizing NP cells report high glucose culture medium (25 mM or 4.5 g/L).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our predictive models are in good agreement with the latter and are more plausible in terms of sustaining the NP cell population which has been shown to experience significant cell death when glucose drops below 0.5 mM for more than 3 days 38,39,109 . Even with an array of predicted and measured glucose concentrations (0.25‐3.5 mM) it is a relatively narrow range confined by the upper supply limit of blood glucose levels (2.6‐6.1 mM) 32 . Despite this more than 50% of publications utilizing NP cells report high glucose culture medium (25 mM or 4.5 g/L).…”
Section: Discussionsupporting
confidence: 58%
“…NP diffusivity reduces with diminishing hydration; anisotropic AF diffusion is captured within the shaded range, with higher diffusivity in the axial direction and lower in the radial direction; CEP diffusivity reduces in the presence of calcification (V max = 14.1 nmol/Â10 6 cells/h and K m = 15 μM). 114 Similar to previous numerical models, [69][70][71] it was assumed that glucose and oxygen concentrations at the disc boundary are that of blood plasma in the surrounding blood vessels, 5.33 mM 32…”
Section: Establishing In Silico Models As a Function Of Degeneration ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A follow-up of blood glucose distribution characteristics in a health examination population in Chengdu, China, from 2010 to 2016 showed higher glucose levels with increasing age, and males had higher glucose levels than females [ 16 ]. Likewise, the mean level of FPG significantly increased across age groups in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a significant variability of FPG caused by month, age, or gender. A follow-up of blood glucose distribution characteristics in a health examination population in Chengdu, China, from 2010 to 2016 showed higher levels of glucose with ages increasing, and males indicated higher expression of glucose than that in females [16]. Likewise, the mean level of FPG significantly increased across age groups in both males and females.…”
Section: Discussionmentioning
confidence: 94%